Increased survival of honey bees consuming pollen and beebread is associated with elevated biomarkers of oxidative stress - Yazlovytska, Liudmyla S.; Karavan, Volodymyr V.; Domaciuk, Marcin; Panchuk, Irina I.; Borsuk, Grzegorz; Volkov, Roman A. (Frontiers in Ecology and Evolution, 2023)
Significant losses of honey bee colonies have been observed worldwide in recent decades. Inadequate nutrition is considered to be one of the factors that can reduce honey bee resistance to abiotic and biotic environmental stresses. Accordingly, we compared six diet variants to assess the impact of food composition on worker bee survival. After 17 days of feeding, the lowest mortality was observed in the group of bees that received sucrose solution with the addition of willow pollen or artificial rapeseed beebread or artificial willow beebread (diets 4, 5 and 6). The highest mortality was found in bees that consumed only sucrose solution (diet 1) or the sucrose solution supplemented with a mixture of amino acids (diet 2), which can be explained by the lack of vitamins and microelements in these diets. In the group of bees that received the sucrose solution with rapeseed pollen (diet 3), mortality was intermediate. To check whether the decrease in insect survival could be related to oxidative damage, we evaluated biomarkers of oxidative stress. Consumption of pollen (diets 3 and 5) and artificial beebread (diets 4 and 6) enhance protein carbonylation in worker bees. Feeding bees artificial beebread also resulted in increase in lipid peroxidation and catalase activity, which is probably due to the presence of hydrogen peroxide in the honey contained in beebread. Remarkably, the increase in biomarkers of oxidative stress was not accompanied by adverse but positive effects on insect survival. A lack of amino acids and proteins in the diet 1 did not cause oxidative stress, but led to an increase in lysozyme activity in hemolymph, a biomarker of immune system status. In conclusion, we believe that the increase in oxidative stress biomarkers we found do not indicate oxidative damage, but rather reflect the changes in redox balance due to consumption of certain dietary options.